Application of active remote sensing in confirmation rights and identification of mortgage supply-demand subjects of rural land in Guangdong Province. (12th March 2021) - Hu, Shanshan; Fu, Zhaogang; Jackson Samuel, R. Dinesh; Anandhan, Prathik
ABSTRACT: In recent years, the remote sensing data plays an increasingly significant role in Land use prediction modeling. The effects of land conversion and agricultural bio production are evaluated using remote sensing and economic analysis. It is impossible to over-emphasize the advantages of the vibrant, efficient hybrid mortgage market in Guangdong as it is inseparably linked to economic development. This paper explores specifically the main variables affecting residential mortgage demand and other restrictions on households' use of a mortgage using the Fuzzy Systematic Evaluation System (FSES). Furthermore, this objective has been accomplished by examining and analyzing the available mortgage products in Guandong through questionnaire survey responses. In addition, the high-interest rates, low income, and house prices result in high and unreasonable repayment-to-earnings mortgages ratios. Moreover, the cumulative effect of this is to make households on low and mid-income prices to the mortgage market. While higher house prices are found in this study to increase mortgage demand, they trigger banks to offer fewer and charge higher rates, particularly after the boom, and especially for highly leveraged households.